What everyone needs to know about Islam - Esposito, John L. (Oxford University Press, 2011)
"Since the terrorist attacks of September 11th, there has been an overwhelming demand for information about Islam, and recent events such as the war in Iraq, terrorist attacks both failed and successful, debates throughout Europe over Islamic dress, and many others, have raised new questions in the minds of policymakers and the general public. This newly updated edition is a source for clearly presented, objective information about these new developments, and for answers to questions about the origin and traditions of Islam. The author is one of America's leading authorities on Islam. This book contains up-to-date information on the faith, customs, and political beliefs of the more than one billion people who call themselves Muslims."--Provided by publisher.